Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 5. Speech outcomes in 5-year-olds - consonant proficiency and errors. Issue 1 (2nd January 2017) - Willadsen, Elisabeth; Lohmander, Anette; Persson, Christina; Lundeborg, Inger; Alaluusua, Suvi; Aukner, Ragnhild; Bau, Anja; Boers, Maria; Bowden, Melanie; Davies, Julie; Emborg, Berit; Havstam, Christina; et al.
Abstract: Background and aim: Normal articulation before school start is a main objective in cleft palate treatment. The aim was to investigate if differences exist in consonant proficiency at age 5 years between children with unilateral cleft lip and palate (UCLP) randomised to different surgical protocols for primary palatal repair. A secondary aim was to estimate burden of care in terms of received additional secondary surgeries and speech therapy. Design: Three parallel group, randomised clinical trials were undertaken as an international multicentre study by 10 cleft teams in five countries: Denmark, Finland, Norway, Sweden, and the UK. Methods: Three different surgical protocols for primary palatal repair were tested against a common procedure in the total cohort of 448 children born with non-syndromic UCLP. Speech audio- and video-recordings of 391 children (136 girls and 255 boys) were available and transcribed phonetically. The main outcome measure was Percent Consonants Correct (PCC) from blinded assessments. Results: In Trial 1, arm A showed statistically significant higher PCC scores (82%) than arm B (78%) ( p  = .045). No significant differences were found between prevalences in Trial 2, A: 79%, C: 82%; or Trial 3, A: 80%, D: 85%. Across all trials, girls achieved better PCC scores, excluding s-errors, than boys (91.0% and 87.5%, respectively) ( p  = .01). Conclusions: PCC scores were higher in arm A than B in Trial 1, whereas no differences were found between arms in Trials 2 or 3. The burden of care in terms of secondary pharyngeal surgeries, number of fistulae, and speech therapy visits differed. Trial registration: ISRCTN29932826.